2019
DOI: 10.2174/0929867324666170920144130
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceuticals and "Repurposed" Drugs of Phytochemical Origin in Prevention and Interception of Chronic Degenerative Diseases and Cancer

Abstract: A long history of research has pursued the use of embryonic factors isolated during cell differentiation processes for the express purpose of transforming cancer cells back to healthy phenotypes. Recent results have clarified that the substances present at different stages of cell differentiation-which we call stem cell differentiation stage factors (SCDSFs)-are proteins with low molecular weight and nucleic acids that regulate genomic expression. The present review summarizes how these substances, taken at di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 243 publications
(103 reference statements)
0
18
0
Order By: Relevance
“…We suggest to combine ICBs with drugs that inhibit VEGF ( 232 ) or to employ drugs that eliminate the protumor inflammatory cells (for example, trabectedin to eliminate TAMs) or to treat with anti-inflammatory agents that will “re-polarize” the immune cells, for example, the repurposed drugs (metformin) and phytochemicals and their synthetic derivatives (CDDO-Im and XN) or both. Since phytochemicals and their synthetic derivatives often protect the cardiovascular system from chemotherapy induced damage ( 248 , 263 , 264 ), we propose, as a first-line therapy for difficult and metastatic tumors, to pretreat with phytochemicals or synthetic derivatives, then continue treatment and add sequentially a VEGF blocker, ICBs, and chemotherapy (to trigger the immunogenic cell death). This will set the stage for the ICBs to become highly effective in additional patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We suggest to combine ICBs with drugs that inhibit VEGF ( 232 ) or to employ drugs that eliminate the protumor inflammatory cells (for example, trabectedin to eliminate TAMs) or to treat with anti-inflammatory agents that will “re-polarize” the immune cells, for example, the repurposed drugs (metformin) and phytochemicals and their synthetic derivatives (CDDO-Im and XN) or both. Since phytochemicals and their synthetic derivatives often protect the cardiovascular system from chemotherapy induced damage ( 248 , 263 , 264 ), we propose, as a first-line therapy for difficult and metastatic tumors, to pretreat with phytochemicals or synthetic derivatives, then continue treatment and add sequentially a VEGF blocker, ICBs, and chemotherapy (to trigger the immunogenic cell death). This will set the stage for the ICBs to become highly effective in additional patients.…”
Section: Discussionmentioning
confidence: 99%
“…In experimental models, we showed that aspirin or the beta-blocker agent atenolol can augment the activity of metformin, a biguanide largely employed in type 2 diabetes management and that have been associated to reduced risk of developing diverse cancers, including breast cancers (Figure 4 ), targeting both neoplastic cells and the TME ( 246 , 247 ). Metformin and phenformin affect the angiogenesis pathway ( 248 250 ) and modulate the immune response and the microbiome ( 251 , 252 ). Phenformin enhances PD-1 immunotherapy ( 115 ).…”
Section: Pharmacological and Immunotherapeutic Combination Targeting mentioning
confidence: 99%
“…Adherence to a Mediterranean dietary pattern has generally been associated with a decreased risk of developing most non-communicable diseases, including cardiovascular, neurodegenerative pathologies, and cancer [1,2,3,4]. This has led to active exploration of whole and isolated products from different naturally occurring sources in various preclinical and clinical settings [5,6,7,8,9]. Chemopreventive activities of diverse diet-derived phytochemicals have been widely studied in the most common cancers, including lung, colon, breast, and prostate.…”
Section: Introductionmentioning
confidence: 99%
“…Chemopreventive activities of diverse diet-derived phytochemicals have been widely studied in the most common cancers, including lung, colon, breast, and prostate. Chemopreventive agents are natural or synthetic agents that prevent or delay cancer development, progression, and/or recurrence [5,6,7], and many natural products and dietary agents have chemopreventive properties. These chemopreventive activities include anti-inflammatory and antioxidant properties [5,6,10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In studies comparing free and nano encapsulated curcumin, the bioavailability and effect of curcumin were greatly increased in terms of anti-inflammatory action [ 16 , 17 ]. The mechanism of action of these nutraceuticals are based on cell cycle regulation, tyrosine kinase modulation [ 18 ] inhibition of cytokine and interleukin secretion, and AMPK-Sclerosis Tuberous Complex (TSC) activation with consequent AKT-mTOR axis inhibition [ 19 ]. However, the clinical use of these nutraceuticals is limited by their low oral bioavailability due to oxidation in biological environments, which results in a low accumulation in the cell cytoplasm [ 20 ].…”
Section: Introductionmentioning
confidence: 99%